Intrinsic defects in nonstoichiometric B-SiC nanoparticles studied by pulsed magnetic resonance methods - Savchenko, D.V.; Pöppl, A.; Kalabukhova, E.N.; Venger, E.F.; Gadzira, M.P.; Gnesin, G.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Nonstoichiometric B-SiC nanoparticles (np-SiC) have been studied by electron
paramagnetic resonance (EPR) and pulsed magnetic resonance methods including field
swept electron spin echo (FS ESE), pulsed electron nuclear double resonance (ENDOR)
and hyperfine sublevel correlation spectroscopy (HYSCORE). Four ESE signals related
to the paramagnetic centers labeled D1, D2, D3, D4 with g = 2.0043, g = 2.0029,
g = 2.0031, g = 2.0037 were resolved in FS ESE spectrum due to their different spin
relaxation times. As deduced from the study of the superhyperfine structure of the D2
defect by FS ESE, pulse ENDOR and HYSCORE methods the dominant paramagnetic
center is a carbon vacancy (Vc) localized in B-SiC crystalline phase of the np-SiC. The
parameters of the D2 center coincide with those found for the Vc in np-SiC obtained by
laser pyrolysis method. Three other defects were identified by comparison of their EPR
parameters with the microstructure of the np-SiC. The D1 defect was attributed to the Vc
vacancy located in a-SiC crystalline phase. The D3 defect is identified with the carbon
dangling bonds located in the carbon excess phase. The D4 defect was assigned to a
threefold-coordinated Si atom bonded with one nitrogen atom, resulting in the formation
of the local bonding Si-Si2N configuration in a-Si3N4 phase.